Naoxintong Capsule Alternates Gut Microbiota and Prevents Hyperlipidemia in High-Fat-Diet Fed Rats - Lu, Yihang; Wan, Haofang; Wu, Yujia; Yang, Jiehong; Yu, Li; He, Yu; Wan, Haitong; Li, Chang (Frontiers in Pharmacology, 2022)
Background: Naoxintong Capsule (NXT) is a formulated Traditional Chinese Medicine (TCM) widely applied in the treatment of cardiovascular and metabolomic diseases, most of which are closely related to hyperlipidemia as a major risk factor. Methods: The chemical components of NXT were firstly analyzed with HPLC-MS method. In high fat diet (HFD)-fed rat models, as well as normal rats as control, the histopathological and biochemical changes of serum and liver were examined, including total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C). In addition, the gut microbiota community was analyzed using 16S rRNA sequencing technique, the fecal levels of gut microbiota related metabolites, including bile acids (BAs) and short chain fatty acids (SCFAs) were determined with HPLC-MS. The correlations of the clinical indicators and gut microbiota related indicators were then investigated statistically. Results: The results showed that NXT exerts potential preventive effect on hyperlipidemia. The body weight, serum lipid levels and liver function were all significantly alleviated. The gut microbiota of the HFD-fed rats were reconstituted with supplementation of NXT. The fecal levels of gut microbiota related metabolites, including BA and SCFA were also altered. The correlation between the gut microbiota and clinical/metabolomic parameters was then studied to reveal potential therapeutic biomarkers of NXT. Conclusions: NXT was effective in regulation of gut microbiota and prevention of hyperlipidemia in HFD fed rats. The present work might provide novel insights into the anti-hyperlipidemia effects of traditional Chinese medicine (TCM) and afford new scientific evidence for clinical application of TCM.